Sustainable development in technological and vocational higher education: balanced scorecard measures with uncertainty. (1st May 2016) - Lin, Mei-Hui; Hu, Jiayao; Tseng, Ming-Lang; Chiu, Anthony S.F.; Lin, Chunyi
Abstract: Technological and vocational education plays an important, long-term role in the industrial development of Taiwan. This study benchmarks the sustainable development competencies required by the future technological and vocational higher education and provided details how sustainability issues can be integrated into a modified balanced scorecard model for industrial–academic cooperation. This study aims to integrate performance and importance levels using quantitative and qualitative information with a modified balanced scorecard model, which incorporates expert perceptions by applying the fuzzy Delphi method, a final performance score and an analytical network process to evaluate the interdependent relations within a closed-loop hierarchical structure. The findings of the study provide an insight into the attributes of the modified model. Specifically, industrial leadership, student acquisition and the cost of service quality comparisons provide knowledge related to those institutions and indicate that the strategic plan for sustainable development is particularly helpful for enhancing the stakeholder relationship and developing a shared understanding of the inter-stakeholders. Highlights: This study aims to benchmark the SD competencies for TVHE professionals. The SD integrated into the modified balanced scorecard model. A model contains quantitative and qualitative measures under uncertainty. The industrial leadership and service quality comparisons ranked as top priority.